Analisa Terhadap Efektivitas Peraturan Mahkamah Agung Nomor 2 Tahun 2015 tentang Tata Cara Penyelesaian Gugatan Sederhana - Yudhi Priyo Amboro; Okta Feryanto (Fakultas Hukum, Universitas Internasional Batam, 2016)
In order to create judicial mechanism more simpler, faster and cheaper on dispute settlement procedure, therefore the Supreme Court Regulation Number 2 Year 2015 regarding Settlement Procedures of Small Claim Court was promulgated. This research aim to understand how the regulation regarding Settlement Procedures on simple lawsuit had been implemented at Batam District Court, to find out the obstacles and also to review the efectivity of the regulations to reach legal desirebility of the parties pertaining the court decision. This research is a juridical normative legal research using qualitative and descriptive method. Source of data used are secondary data, namely literary study and primary data namely interview. Upon the collection of all literary study, then such data shall be processed and analized, and then the primary data from the interview is used as adjustment of the research data result. Further, the conclusion related to this research shall be drawn, and then the legal effectivity of the Supreme Court Regulation Number 2 Year 2015 in the District Court of Batam shall be descriptively elaborated. This research result that upon the promulgation, a number of 17 Small Claim Court cases had been settled in the District Court of Batam for the year 2016 alone. Notwichtstanding there are significance number of case has been processed, there are some problems in the implementation of the examination session of the Small Claim Court in the District Court of Batam, one of them is that there are no verdict which are executable. However, beside from such problems, the settlement of Small